Department of Pathophysiology of Siberian State Medical University: 120th anniversary of scientific and pedagogical activity - O. I. Urazova; S. A. Nekrylov (Бюллетень сибирской медицины)
The article is dedicated to the 120th anniversary of the foundation day of the Department of General Pathology (Pathophysiology) of the Imperial Tomsk University - Tomsk Medical Institute - Siberian State Medical University and scientists whose scientific and pedagogical activity as well as career paths are connected with the Department and Tomsk Cathedral Scientific School of Pathophysiologists, one of the oldest schools in Russia and the first one in the Asian part of Russia. Main directions of school's scientific and research work of the past years are described in the article as well as its present day achievements in science. Special attention is paid to the activity of the head directors and the best representatives of the Tomsk Pathophysiological School such as P.M. Albitsky, A.V. Reprev, D.I. Timofeevsky, P.P. Avrorov, A.D. Timofeevsky, L.F. Larionov, D.I. Goldberg, E.D. Goldberg, V.S. Lavrova, who made a significant contribution to the development of the Russian medical science and medical education. The data on the leading scientific school of the Russian Federation under the leadership of the RAMS Academician V.V. Novitsky is presented in the article.